Możliwości rozwoju obszarów wiejskich Dolnego Śląska na przykładzie wybranych gmin - Kutkowska, Barbara (Possibilities of the Development of Rural Areas of Lower Silesia on the Example of Selected Communes, 2005)
This paper shows the actual situation and adaptation possibilities of farms, which are situated on two communes of Lower Silesia region: Wisznia Mała and Kobierzyce. The possibilities of development of typical agricultural production, small enterprises, and other non-agricultural activities are evaluated in this research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 545-548